Numerical Algorithm for A Computational Experiment for An Applied Optimization Problem in Systems with Distributed Parameters - Suvonov O. O (Genius Publishing Group, 2023)
The paper considers the optimization problem that takes place in the optimal control of oil production, where the state of the system is described by equations of the elliptic type. A two-stage algorithm for solving the problem with the proof of theorems on qualitative estimates of iterative processes is presented
Keywords: optimization; optimal control; oil production